A mechanistic perspective on the kinetics of plastic deformation in FCC High Entropy Alloys: Effect of strain, strain rate and temperature. (May 2021) - Raturi, Abheepsit; Biswas, Krishanu; Gurao, N.P.
Abstract: Strain rate sensitivity and activation volume that dictate the kinetics of plastic deformation along with strain hardening response determine the plastic deformation behaviour of novel high entropy alloys. Although, the deformation behaviour of FCC single-phase Cantor alloy exhibits some similarity to that of conventional FCC solid solutions, the deformation behaviour over a wide range of temperature, strain rate, strain and grain size is unexplored. More importantly, theoretical understanding of solid solution strengthening, stacking fault energy and dislocation activation in 100 percent solute high entropy alloys (HEAs) and their flow kinetics is not yet established. This necessitates development of combined experimental and computational approaches to realise the mechanistic design of new single-phase and multi-phase transformative FCC HEAs to achieve optimum combination of strength and ductility in the novel complex concentrated alloys. Graphical abstract: Image, graphical abstract